Mrs. Patricia Bessent honored with volume (Raton Range Raton, New Mexico, 1966)
Article on Mrs. Patricia Bessent who has been honored in a chapter of Lew Wallaces Daughters of the American Revolution.
Master list item #:36
File location is in the Raton File Cabinet
Keywords: Bessent, Patricia; Gladys, Patricia; Bessent, Martin; Martin, Ben; Martin, Ben (Mrs.); DAR Library; Local History; Biography; Book Chapter; American Revolution; Flag of the United States Committee; Raton, New Mexico; Washington, D.C.